THE IMPACT OF SUSTAINABLE SUPPLY CHAIN PRACTICES ON CORPORATE SOCIAL RESPONSIBILITY IN THE GLOBAL TEXTILE INDUSTRY - Ahmed, Md Foysal; Khan, Waqas Ahmed; Wafik, H M Atif; Mahbub, Salehin; Morshed, Arik; Rahman, Muhammad Aminur (Journal of Posthumanism, 2024)
This study examines the impact of sustainable supply chain practices and circular economy on CSR performance in the global textile industry. More importantly, it analyzes the moderating effects of regulatory policies and complianceincluding consumer awareness and ethical demand on the CSR performance. The quantitative methods with the helpof survey on textile firms as the population sample to which 2555questionnaires were distributed,with a resultant 1533 valid returns. Structural equation modeling (SEM) with AMOS was used to analyze the data based on the regulatory and moderating variables identified and tested. Research suggests both Sustainable Supply Chain Management (SSCM)and Circular Economy Practices (CEP)positively and significantly influence CSR performancein the global textile industry. However, the moderating roles of regulatory policies and consumer awareness appear to be weak, suggesting that external pressure alone is insufficient to drive substantial CSR improvementsin the global RMG’s.TheSSCM and CEP practices, while limited, do enhance CSR performance in the textile industry. Regulatory policies along with consumer awareness have little moderating impact, signaling the importance of moving from compliance to integrating sustainability into businessThe imbalance between consumer awareness and CSR integration must be addressed to enhance ethical and environmental performance.